Integrating Reinforcement Learning in Software Testing Automation: A Promising Approach - Lima, Diogo Florencio de; Albuquerque, Danyllo; Dantas Filho, Emanuel; Perkusich, Mirko; Perkusich, Angelo (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE), 2023)
In the rapidly evolving landscape of software development, ensuring reliable and efficient software systems is essential. However, traditional software testing methods often struggle to achieve comprehensive test coverage and adaptability to changing software dynamics. To address these challenges, this paper proposes an innovative approach that integrates reinforcement learning techniques into software testing automation. Our goal is to enhance test generation and prioritization strategies, leading to improved fault detection, adaptability, and resource utilization. By developing an intelligent testing framework that learns from feedback received during the testing process, we optimize test coverage and fault detection using reinforcement learning. Initial experiments demonstrate the potential of our approach in improving software testing outcomes. The integration of reinforcement learning into software testing automation holds promise for advancing the field, enabling more reliable and adaptable software systems, and reducing development costs.